1999
DOI: 10.1892/0891-6640(1999)013<0036:eoptsa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passive Transfer Status and Vaccination with Escherichia coli (J5) on Mortality in Comingled Dairy Calves

Abstract: The effect of vaccination with a commercially available R-mutant coliform mastitis vaccine on the survival of comingled dairy calves on a farm with endemic salmonellosis was examined. A total of 864 calves were randomly assigned to either vaccine (n = 435) or control (n = 429) groups. Passive transfer status of each calf was determined using refractometer determination of serum total protein concentration. Logistic models were developed to determine the effects of vaccine group and passive transfer status on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Traditional research in Holstein calves has established cutoff values for FPT at IgG concentration at 1,000 mg/dL in serum [14], which has [5,[20][21][22][23][24]. As in previous studies [19,21,22], we found that serum IgG and TP concentrations were correlated, but less so than in other studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Traditional research in Holstein calves has established cutoff values for FPT at IgG concentration at 1,000 mg/dL in serum [14], which has [5,[20][21][22][23][24]. As in previous studies [19,21,22], we found that serum IgG and TP concentrations were correlated, but less so than in other studies.…”
Section: Discussionsupporting
confidence: 58%
“…This relationship allows measuring serum TP concentration via refractometer under field conditions as a proxy for IgG concentration. Using the commonly accepted cutoff limit of 1,000 mg/dL of IgG to define FPT has resulted in a broad variation in cutoff values for serum TP in Holstein calves between 5.0 and 5.5 g/dL [5,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Total protein in plasma, particularly when estimated by refractometry, has commonly been used to estimate the acquisition of passive immunity in newborn calves fed colostrum Tyler et al, 1999). The correlation between plasma total protein and plasma IgG in neonates is usually sufficient to allow adequate estimation of status of passive transfer.…”
Section: Discussionmentioning
confidence: 99%
“…High mortality risks (8.2%) have been reported in farms which purchase young calves from different origin [41]. Surprisingly, the mortality risk in veal calves was similar to live born calves in dairy replacement herds in Great Britain (5.0%), Norway (4,6%), Sweden (4.0%) and crossbred cow-calf farms in Switzerland (5.0%) and even smaller than reported in large scale dairy calf rearing in Northern America (7,6% and 13,3%) [2,3,7,9,35,42].…”
Section: Diseasementioning
confidence: 99%